Tamalola; Transregional connectivities, Islam, and anti-colonialism on an Indonesian island - Hägerdal, Hans; Wellfelt, Emilie (UI Scholars Hub, 2019)
The present study focuses on a set of events in the Aru Islands, Maluku, in the late eighteenth century which are documented in some detail by Dutch records. A violent rebellion with Muslim and anti-European overtones baffled the Dutch colonialists (VOC) and led to a series of humiliations for the Company on Aru, before eventually being subdued. As one of the main catalysts of the conflict stands the chief Tamalola from the Muslim island Ujir. Interestingly, this person is also a central figure in local traditions from Ujir. Moreover, his story connects with wider cultural and economic networks in eastern Indonesia. Thus the article asks how the imprints of the Tamalola figure in textual and non-textual sources can add to our knowledge of how communities of Eastern Indonesia ordered their lives outside colonial control.